Monitoring of the diamondback moth (Plutella xylostella L.) on the Brassica oleracea L. collection in the vicinity of St. Petersburg - Yu. A. Zakharova; A. N. Frolov; A. M. Artemyeva (Труды по прикладной ботанике, генетике и селекции, 2022)
Background. Diamondback moth (Plutella xylostella L.) has now acquired the status of the most dangerous pest of plants from the Brassicaceae family in the world, including Russia. In order to identify genotypes resistant to the pest, cabbage accessions from the VIR global collection were assessed in the field according to plant infestation and damage by diamondback moth in the vicinity of St. Petersburg.Materials and methods. The infestation of plants by diamondback moth was assessed on model accessions when examining all plants in the plot by (1) the number of larvae and pupae, and (2) leaf damage, assessed using a standard scoring scale. The number of adults was monitored using sticky Delta traps of two designs: (1) cardboard traps equipped with commercial dispensers with synthetic sex pheromone, and (2) plastic LED traps designed at VIZR.Results. The results of field surveys attested to very high variation among cabbage accessions in the rates of infestation and damage to plants caused by diamondback moth. The data on the abundance of adults caught by pheromone traps correlated well with the estimates of larval and pupal density of the pest on plants. The capture rate of diamondback moths with LED traps varied greatly during the season. In June/early July, i.e., during the period of the so called “white” nights, LED traps caught diamondback moths much worse than pheromone ones, but during the second half of July and August their capture rate significantly exceeded that of pheromone traps. As a result, the relationship between numbers of diamondback moth larvae on plants and adults in LED traps turned out to be negative. Conclusion. The resulting materials indicate obvious prospects of studying the VIR global collection in order to identify sources of host plant resistance to diamondback moth. The abundance of this pest in northern regions of its spreading is recommended to be controlled with pheromone traps.